2020
DOI: 10.1029/2020gl090548
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface Evolution and Persistence of Marine Heatwaves in the Northeast Pacific

Abstract: The reappearance of a northeast Pacific marine heatwave (MHW) sounded alarms in late summer 2019 for a warming event on par with the 2013-2016 MHW known as The Blob. Despite these two events having similar magnitudes in surface warming, differences in seasonality and salinity distinguish their evolutions. We compare and contrast the ocean's role in the evolution and persistence of the 2013-2016 and 2019-2020 MHWs using mapped temperature and salinity data from Argo floats. An unusual near-surface freshwater an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(102 citation statements)
references
References 37 publications
8
94
0
Order By: Relevance
“…The authors linked the deepest MHWs (800 m) to anticyclonic eddies in the Tasman Sea and found that they were more prominent in winter. Sub-surface warming has also been shown to linger well after the surface signal has disappeared, indicating that the ocean sub-surface maintains long-term temperature memory (Jackson et al, 2018;Scannell et al, 2020). These findings are consistent with the biological impacts observed from the surface down to benthic communities (Marzinelli et al, 2015;Short et al, 2015).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…The authors linked the deepest MHWs (800 m) to anticyclonic eddies in the Tasman Sea and found that they were more prominent in winter. Sub-surface warming has also been shown to linger well after the surface signal has disappeared, indicating that the ocean sub-surface maintains long-term temperature memory (Jackson et al, 2018;Scannell et al, 2020). These findings are consistent with the biological impacts observed from the surface down to benthic communities (Marzinelli et al, 2015;Short et al, 2015).…”
supporting
confidence: 76%
“…Although, Adv'-MHWs are not necessarily describing eddy structures, those instances agree with results from Elzahaby and Schaeffer (2019), which showed that the deepest MHWs were associated with ocean advection through anticyclonic eddy structures in a region similar to the Eddy box. While the link between deep MHWs and eddies could be explained by isopycnal heave (Scannell et al, 2020), preliminary analysis showed no clear pattern between Adv'-MHWs and heave. In fact, spice could be an important factor in the region.…”
Section: Mhw Depthmentioning
confidence: 75%
See 1 more Smart Citation
“…Upwelling causes deep‐water renewal in all four inlets (Baker & Pond, 1995; Hodal, 2010; Lafond & Pickard, 1975; Wan et al., 2017). Upwelled water travels from the NE Pacific to Rivers Inlet along the 1,026 kgm −3 isopycnal (Hare et al., 2020) and both offshore and deep Rivers Inlet water were anomalously warm following the 2014–2016 marine heatwave (Jackson et al., 2018; Scannell et al., 2020), which accelerated the warming trend after 2016 (Figure 2a and Table 1). Rivers Inlet deep water is significantly denser than waters in Bute or Knight Inlet, yet the fact that some of the warmest deep waters in Bute and Knight Inlet were observed after 2017 suggests that, similar to Rivers Inlet, the source waters for Bute and Knight Inlet also warmed.…”
Section: Discussionmentioning
confidence: 99%
“…To classify MHWs, we used the definition presented in (Scannell et al, 2020) which defines MHW as an event when SST exceeds the monthly climatological 90th percentile for at least a month using monthly data from January 1986 to December 2020. To detect MHWs in the OISST dataset we used the Python package Ocetrac (Scannell et al, 2021).…”
Section: Methodsmentioning
confidence: 99%